Menggali Potensi Zakat di Daerah: Studi Analisis-Kualitatif di Kabupaten Bekasi - Yoyo Hambali (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
This article aims to explore the potential of zakat in Bekasi. Zakat is viewed as “compulsory charity”; it is an obligation for those who have received their wealth from God to respond to those members of the community in need. Zakat must be paid on different categories of property — gold, silver, money; livestock; agricultural produce; and business commodities — and is payable each year after one year’s possession. It requires an annual contribution of 2.5 percent of an individual’s wealth and assets. As a buffer state capital, with a population of Bekasi 2.2 million has considerable economic potential zakat as an instrument for extracting local government in realizing its vision of "Leading The religious community in the field of Industry, Commerce, Agriculture and Tourism". Therefore, through qualitative analysis found that the agriculture, fisheries and marine; industrial sector which has 18 industrial areas consisting of large and medium industries, and small industries with a superior product, and trade and investment are affected by some type of effort required zakat maal. Based on the studies conducted, the potential of zakat in Bekasi district that can be assembled to achieve the range of Rp 80 billion to Rp 90 billion per year. The very large number if managed optimally.